Sensory and molecular characterisation of the protective effect of storage at -80 degrees C on the odour profiles of human milk - Sandgruber, Stefanie; Much, Daniela; Amann-Gassner, Ulrike; Hauner, Hans; Büttner, Andrea (Food Chemistry, 2012)
The aim of this study was to investigate if storage at -80 degrees C prevents off-odour formation from oxidative fatty acid degradation, as previously observed for storage at -19 degrees C. This was carried out on milk from mothers being supplemented with fish oil, as well as on milk from those receiving no supplementation (control group). The rationale for this approach was that human milk fatty acid profiles have previously been shown to be highly influenced by maternal fatty acid dietary intake. Also, (poly)unsaturated fatty acids have been shown to be the precursors for off-odour generation during storage at -19 degrees C. Therefore, determination of aroma marker odourants originating from unsaturated fatty acids was performed on milk from both groups that had been stored at -80 degrees C, showing that, unlike the previously reported dramatic flavour changes in human milk stored at -19 degrees C, aroma profiles of milk from both groups remained generally unmodified after storage at -80 degrees C. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Breast milk; Two-dimensional high resolution gas chromatography; Mass spectrometry; Olfactometry; Quantification; Fish oil; Supplementation; Off-odour; Milk banking; Stable isotope dilution assays